Rebuttal to M. E. Hassani's ``Foundations of Superluminal Relativistic Mechanics'' - Sfarti, Adrian (Communications in Physics, 2018)
M. E. Hassani tries to construct the foundations for a superluminal mechanics. In the following note we will prove the premise of his paper to be wrong, rendering his whole paper as incorrect.